Survey of clot waveform analysis of normal activated partial thromboplastin time in patients with cirrhosis and sepsis at Le Van Thinh hospital - Tran Qui Phuong Linh; Nguyen Thi Nhan; Le Minh Thuan; Le Trung Phuong (PLoS ONE, 2025)
This study aimed to establish the correlation between activated partial thromboplastin time (aPTT) in seconds and ratio, first derivative peak (Max1), second derivative peak (Max2), second derivative minimum peak (Min2), and delta-OD of clot waveform analysis in patients diagnosed with cirrhosis, sepsis, and a control group. The study involved a series of cases using the Bayesian ANOVA model with Bayes factor (BF) estimated using the Markov Chain Monte Carlo sampling method with 2 chains. Each chain consisted of 10 000 repetitions and started 5 000 times to predict the variables aPTT (s), aPTT (ratio), Max1, Max2, Min2, and delta-OD respectively across the 3 study groups. The model used was variable ~ stage – 1. This analysis illustrates the adjustment of the posterior proportion for multiple testing by setting the prior probability of the initial hypothesis to 0.5 for all comparisons. There is insufficient evidence that aPTT (s), aPTT (ratio), and Min2 differ between the study groups (0 < BF < 3). There is compelling evidence for the Max1 value in both the sepsis group and the control group (BF10 = 44.042). Additionally, between the sepsis group and the cirrhosis group, there is substantial evidence for the Max1 value (BF10 = 5.842). Moreover, there is convincing evidence for the Max2 value in the sepsis group compared to the control group (BF10 = 38.782). There is almost confirmatory evidence that the delta-OD value in the sepsis group is higher than that in the control group (BF10 = 1251.781). Finally, there is convincing evidence that the sepsis group has a higher delta-OD value than the cirrhosis group (BF10 = 35.555). The Max1, Max2, and delta-OD indices effectively reflect coagulation disorders in patients with cirrhosis and sepsis, even when the aPTT test results are within normal limits.